Turning the Tables : Restaurants and the Rise of the American Middle Class, 1880-1920 - Haley, Andrew P. (Book collections on Project MUSE., 2011)
Haley examines the transformation of American public dining at the start of the twentieth century and argues that the birth of the modern American restaurant helped establish the middle class as the arbiter of American culture.